In utero position matters for littermate cell transfer in mice: an additional and confounding source with maternal microchimerism - Giassi, Mathilde; Hemon, Marie F.; Martin, Marielle; Roudier, Jean; Auger, Isabelle; Lambert, Nathalie C. (Frontiers in Immunology, 2023)
Introduction Feto-maternal cell transfer during pregnancy is called microchimerism (Mc). Its persistence in respective hosts is increasingly studied as to its potential role in immune tolerance, autoimmunity, cancer, and degenerative diseases. Murine models with transgenic reporter genes, heterozygously carried by the mother, allow maternal Mc tracking in wild-type (WT) offspring. However, as gestation in mice is multi-embryonic, an exchange of cells between fetuses carrying the same reporter gene as their mother and negative WT littermate, named littermate Mc (LMc), can occur and be confounded with the maternal source. We propose here to evaluate LMc contribution in mice. Methods To avoid the maternal confounding source of Mc, transgenic males, heterozygous for a reporter gene, here, the human leukocyte antigen DRB1*04 (DR4+/−), were crossed with WT females (DR4−/−). DR4+/− LMc was specifically quantified by HLA-DR4 quantitative PCR, i) in utero in main organs from 15 DR4−/− fetuses from three litters of 11, nine, and five; and ii) after birth in two litters of eight pups: in two DR4−/− stillborns and four DR4−/− adult mice. Results At embryonic stages, DR4−/− fetuses having one or two nearby DR4+/− littermates in the same uterine horn were almost seven times more frequently positive for DR4− microchimerism in their organs (p = 0.01) and had quantitatively more LMc (p = 0.009) than those without nearby DR4+/− littermates. Furthermore, LMc persists at birth and into adulthood with interindividual heterogeneity. Conclusions This study identifies heterogeneity for LMc acquisition according to in utero position and different interpretation of previously published results on maternal Mc in mice.